2019
DOI: 10.47176/mjiri.33.14
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of N-terminal-Pro brain natriuretic peptide in the detection of coronary artery disease in patients with positive myocardial perfusion imaging

Abstract: Background the diagnosis o in the selection between the lev Methods: In Imam Khomei patients on the Results: We stenotic vessel. independently accuracy of 61 and NT-Pro BN Conclusion: CAD and there

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Today, MPI has become a very promising method for brain imaging [335][336][337][338][339][340]. Within a preclinical setting, MPI has proven to be high spatial (more than 46 volumes per second) [323] and temporal resolution (below 1 mm) [327,341] with high sensitivity (with a detection limit of 5 ng of iron) [342,343].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Today, MPI has become a very promising method for brain imaging [335][336][337][338][339][340]. Within a preclinical setting, MPI has proven to be high spatial (more than 46 volumes per second) [323] and temporal resolution (below 1 mm) [327,341] with high sensitivity (with a detection limit of 5 ng of iron) [342,343].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…This indicate different stimulus for synthesis in this two localizations (1). Similarly, other studies showed higher values of this marker in patients with higher oxidative stress: patients with multiple CV risk factors (7) and percutaneous coronary interventions (PCI) in spite of stable intraventricular pressure (8).NT-proBNP can serve as a sensitive marker for diagnosis NSTE-ACS patients (9).It is associated with all AMI, but is a more powerful risk factor for microsize than typical MI (10).NT-proBNP level in patients with AMI is independently associated with extent, severity, and complexity of coronary artery disease assessed by SYNTAX score (12).…”
Section: Discussionmentioning
confidence: 65%
“… 26 the level of NT-proBNP in plasma is significantly positively correlated with the degree of coronary artery stenosis, and it is basically the same as the evaluation of Gensini coefficient, which reflects the condition of coronary artery disease. 27 Moreover, with the increase of the number of diseased coronary arteries, the content of NT-probNP also increased. 28 It was confirmed in the study by D’Amato et al 29 that the serum level of NT-proBNP in the CHD group was significantly higher than that in the non-CHD group.…”
Section: Discussionmentioning
confidence: 98%